Inclusion of the National Professional Standards in Physics Teachers Education Preparation Program in College of Education at King Saud University - Al-Asmari, Hussein Awad; Al-Jabr, Jabr Mohammed (Journal of Educational and Psychological Sciences, 2019)
The objective of this research study was to identify the inclusion level of the national professional standards for teachers in Saudi Arabia in physics teachers’ preparation program in the Faculty of Education at King Saud University. To achieve the objective of the study, the researchers used descriptive analytical method through content analysis. The research sample consisted of the whole population, where the sample included all course syllabuses of physics teachers preparation program at Faculty of Education, King Saud University. The research tools included two lists for analysis: 1) Educational domain, which included four categories, (12) main standards, and (55) sub- standards; and 2) Specialization domain (physics courses), which included seven categories, (16) main standards, and (70) indicators. The reliability of the research tools were assured by Intercoder of analysts (0.87) and (0.90) respectively. Data were collected and statistically processed. The research revealed a number of results, and the most important of which were: professional knowledge in educational domain was the highest with an average of (2.77). On the other hand, electricity and magnetism in specialization domain was the highest with an average of (3.60). Finally, a number of recommendations was suggested, such as reviewing components of physics teachers preparation program in the light of all national professional standards, both educational and specialization domains.
Keywords: National Professional Standards; Physics Teachers; Physics Teachers Preparation Program Courses; Physics Teachers Preparation Program